The Influence of Transformational Leadership, Structural Empowerment and Psychological Well-Being on Work Engagement - Prastyani, Desy; Kaur, Simarjir; Arianti, Yuanita (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2024)
A leader with the right leadership style who performs his duties effectively and efficiently is essential to increase the quality and efficiency of the organization. Transformational leadership motivates followers to perform beyond expectations by awakening followers' higher needs. Transformational leadership plays an important role in creating structural empowerement that can lead to positive organizational outcomes. Structural empowerment is expected to increase the psychological well-being of employees. Work engagement can be shaped by enabling factors such as transformational leadership, structural empowerment and psychological well-being that help create readiness for change. This research therefore aims to examine how transformational leadership can shape work engagement through structural empowerment and psychological well-being. This research is a quantitative study that used a purposive sampling method and included 190 hospital workers in Jakarta, Bogor, Depok, Tangerang, and Bekasi. Data were analyzed using SEM-PLS 3.0 structural equation modeling. The results show that transformational leadership influences work engagement, structural empowerment and psychological well-being. According to the results, employee engagement can be improved by implementing transformational leadership, structural empowerment and psychological well-being in the workplace. The interdependence of these factors creates a productive and positive work environment.